Time, Exposure and Social Sustainability in the National Identity of International Students - Utassy, Luca; Kozma, Dorottya Edina; Horváth, Klaudia Gabriella; Ács, Sarolta (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This study examines how the duration of study abroad is associated with perceived changes in national identity. The aim was to address a gap in understanding whether time spent abroad may be linked to specific attitudinal shifts. The study uses a retrospective pre-post design with 308 international students in Hungary, grouped by time abroad, and analyzes perceived changes across four identity dimensions: national sentiment, patriotism, nationalism, and collective narcissism. While no significant between-group differences emerged, the within-group results suggested that perceived changes were concentrated in the more defensive and superiority-based dimensions of identity. Specifically, a significant decrease in nationalism and a marginal decrease in collective narcissism were observed in the three-or-more-years subgroup, while affective and pride-based dimensions remained stable or showed slight increases. This research contributes by identifying duration as a potentially relevant factor and by distinguishing between different dimensions of national identity in the study abroad context.